The Mystery of Holly Lane - Blyton, Enid (London Dragon Books, 1971)
Who stole the money that the old man in Holly Lane had so carefully hidden in his cottage, and where is it now? Fatty and the Find-Outers are on the case, but it looks as though Mr Goon might solve the mystery first.
Keywords: Five Find-Outers (Fictitious characters) -- Detective and mystery stories -- Children's stories